MANIPULASI AKRUAL DALAM PELAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA: APAKAH GOVERNMENT SIZE DAN KAPASITAS FISKAL MEMILIKI EFEK? - Putri, Mirdaniati; Abdullah, Syukriy; Adnan, Adnan; Yusmita, Fifi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study examines the effect of government size and fiscal capacity on accrual manipulation in local government financial reporting in Indonesia. The sample in this study amounted to 179 districts and cities in Indonesia. The data used is secondary data from local government financial statements (LKPD) for the fiscal year 2020 audited by the Financial Audit Agency (BPK). This study used the Jones Model equation in calculating accrual manipulation. The data analysis method in this study used multiple linear regression analysis with the SPSS version 26 software. The results showed that the variables of government size and fiscal capacity jointly or simultaneously affect the manipulation of accruals in the financial reporting of local governments in Indonesia. Government size has a positive effect and fiscal capacity negatively affects accrual manipulation.